The Influence of Islamic Branding and Product Ingredients on Interest in Buying Sasha Siwak Toothpaste In Ambon City - Zainuddin Latuconsina; Etvin Rizal Tamher; Grace Hoberthina Tahapary; Achmad Syarif Chatib; Uli Wildan Nuryanto (PT Mattawang Mediatama Solution, 2022)
The purpose of this study is to analyze the influence of Islamic branding on buying interest and analyze the influence of product ingredients on buying interest. The data collection technique used is to use questionnaires. The sample in this study was a consumer who used Sasha Siwak toothpaste in Ambon City. The data analysis method used is Partial Least Square (PLS). The results showed that Islamic branding has a positive effect on buying interest and product ingredients also have a positive effect on buying interest.